Regulating Everyday Gambling: A Photo Essay - Bedford, Kate; Shieber, Andrea (feminists@law, 2018)
This photo-essay arises out of a research project undertaken by Kate Bedford and colleagues on gambling regulation, and photographs of a local bingo hall taken by Andrea Shieber as part of an Adult Education photography course. The essay stages a three way dialogue between the photographs, interview data gathered as part of the research project from the case study of bingo regulation in England and Wales, and analysis of what bingo regulation can add to existing debates within political economy. It focuses on two themes: (1) the social, part-domestic nature of the bingo hall and (2) the key role of cash within bingo.